Paradigm shifts - Pierre-André Guy Maugis (Kiel Institute for the World Economy (IfW), 2017)
The author studies the evolution of the number of coexisting beliefs in a financial market in a framework where the paradigm driving the agents' behavior is left unspecified. The overreaching aim is to gain insights regarding the dynamic of the variety of beliefs in an auction based financial market independently of any assumptions on agents' behaviors. The resulting framework may be seen as an abstract agent based model. In a computer experiment he exhibits a cycle between two states, so that either all agents act according to the same belief, or there is no leading belief; i.e., there is one dominating belief, or none. Further, he finds that the frequency of this cycle is positively linked to the quality of the information available to the agents.
Keywords: G40; 330; agent based model; information cascade; herding behavior